Effectiveness of Body Psychotherapy. A Systematic Review and Meta-Analysis - Rosendahl, Sophie; Sattel, Heribert; Lahmann, Claas (Frontiers in Psychiatry, 2021)
Despite the growing relevance and applicability of elements based on and derived from the embodied mind paradigm, body psychotherapy (BPT) is no well-established treatment option. This might be due to a lack of proof for its efficacy. We searched electronic databases (Pubmed MEDLINE, PsycInfo und PSYNDEX) for RCTs examining predefined BPT interventions. 2180 references were screened, of which 113 studies were scrutinized in detail and 18 RCTs finally included. The observed ES demonstrated medium effects of BPT on primary outcomes psychopathology and psychological distress. In case of significant statistical heterogeneity, exploratory subgroup analyses revealed diagnosis and the degree of control group activity as noteworthy moderators. For secondary outcomes evidence was scarce and an improvement could be demonstrated only for coping abilities. The identified evidence indicates that BPT is beneficial for a wide spectrum of psychic suffering. There is a strong need for high-quality studies with bigger samples and for well-defined diagnostic entities to underpin the its effectiveness.